Stochastic model of memristor based on the length of conductive region. (September 2021) - Agudov, N.V.; Dubkov, A.A.; Safonov, A.V.; Krichigin, A.V.; Kharcheva, A.A.; Guseinov, D.V.; Koryazhkina, M.N.; Novikov, A.S.; Shishmakova, V.A.; Antonov, I.N.; Carollo, A.; Spagnolo, B.
Abstract: We propose a stochastic model of a voltage controlled bipolar memristive system, which includes the properties of widely used dynamic SPICE models and takes into account the fluctuations inherent in memristors. The proposed model is described by rather simple equations of Brownian diffusion, does not require significant computational resources for numerical modeling, and allows obtaining the exact analytical solutions in some cases. The noise-induced transient bimodality phenomenon, arising under resistive switching, was revealed and investigated theoretically and experimentally in a memristive system, by finding a quite good qualitatively agreement between theory and experiment. Based on the proposed model, the mathematical apparatus of Markov processes for the first passage time of the boundaries can be used to analyse the temporal characteristics of resistive switching.